Experimental Study on Thermal and Structural Analysis of Tool and Cutter Grinding Operation Using Finite Element Method - Dhull, Vinod (My University, 2010)
Grinding machines remove material from the work piece by abrasion, which can generate substantial amounts of heat. Currently finite element method approach is used by researchers to evaluate results for almost every problem to observe the variation in data in experimental results and simulated results. Finite element approach has made work in different fields like grinding, turning, milling, etc, highly accurate and precise. Tool & Cutter grinders are used to sharpen various cutting tools used on the lathes and milling machines, debur, or used to remove surface imperfections and to work on extremely hard materials. In the present work an attempt has been made to work on thermal and structural analysis of different work pieces using tool & cutter grinder and its analysis following finite element method approach. Finite Element Method (FEM) approach is defined as a computer aided mathematical technique for obtaining approximate numerical solutions to the abstract equation of calculus that predict the response of physical system subjected to external influence. In the present study the comparison has been made between data for experimental study and software study comparing the data for variation of stresses in ABAQUS software and variation of temperature in ANSYS software. Different types of materials like mild steel, high chromium steel and stainless steel are used for further carrying out the study of thermal and structural analysis for the same and to compare the results obtained for experimental studies and simulated studies. Machining operations have been performed using the above mentioned grinder as a machine tool and by varying the different machining parameters such as depth of cut, feed, cutting speed of wheel, the force and temperature which will affect the thermal and structural properties of the work piece will be obtained.
Keywords: Finite Element Method